Geographic Representations - Zhang, Jingxiong; Atkinson, Peter; Goodchild, Michael F. (Scale in Spatial Information and Analysis, 2014)
Scale is a fundamental concept in the geosciences and provides key information on geographic representations, measurements, analysis, and modeling. Thus, studies about representing and integrating spatial data at different scales are important for spatial problem solving (Amrhein and Wong 1996; Longley and Batty 1996; Quattrochi and Goodchild 1997; Atkinson and Tate 2000; Goodchild 2011). As outlined in Chapter 1, geographic conceptualization concerns how spatial entities and distributions should be represented (i.e., in which data models and at what scales) to facilitate discretization, data acquisition and integration, geo-processing, and visualization in a computerized environment, and is fundamental for research on scale in spatial information and analysis. This chapter will describe geographic representations and associated scale issues (e.g., scale dependence of these representation models and representations that are adaptive to scale), based on the conceptual framework laid out by Goodchild et al. (2007).